PEMBELAJARAN KETERAMPILAN MENULIS BAHASA JERMAN MELALUI GOOGLE CLASSROOM SISWA KELAS X IBB SEMESTER I SMAN 1 TARIK - Sari, Suchi Emelda; Wahyuningsih, Fahmi (LATERNE, 2021)
German is a foreign language that is learned in every high school, with cross-interest or compulsory subjects. Students at SMAN 1 Tarik have difficulty in writing German skills, because class X students have not received German language learning during their school years and do not yet know how to write German grammar/sentences/vocabularies. This research is motivated by the difficulties of students in writing German during the covid-19 pandemic, it is necessary to have learning innovations in the form of the application of online learning that can help students in the teaching and learning process. The purpose of this study is to describe or describe the effectiveness of online learning on German writing skills through Google Classroom. This research is a descriptive qualitative research using library data collection techniques, learning outcomes of German writing skills through Google Classroom, and observation. The results showed that learning German for writing skills through Google Classroom was found to be effective. From the results of the assignments, students of class X IBB semester 1 of SMAN 1 Tarik have reached the indicator with a complete score above the KKM as much as 68.75%. From the data obtained, 22 students collected assignments with a percentage of 68.75% and 10 students did not collect assignments with a percentage of 31.25%.